Waves of Extremism: An Applied Ethnographic Analysis of the Bosnia and Herzegovina Football Terraces - Testa, Alberto (Frontiers in Sports and Active Living, 2022)
This paper offers an overview of the results of a four-month research project studying extremism in the Bosnia and Herzegovina (BiH) football terraces conducted in 2019–2020. This work was funded by the International Organization for Migration - United Nations and by the United States Agency for International Development (USAID). The research focused on ‘risk’ factors and how these may govern ‘entry’ of BiH youth into extreme hard-core football fans groups (Ultras ) and prolong their involvement in them. The study aimed to highlight the nature of these groups and their activity providing detailed recommendations for BiH policy makers, security agencies and football federations and clubs who wish to understand and effectively respond to this emergent threat for public security in BiH.